Value Driven Design Revisited: Emerging Modelling Concepts and Applications - Bertoni, Marco; Bertoni, Alessandro; Murat Hakki, Eres (Proceedings of the International Design Society, 2019)
Extended product warranties, leasing, and pay-per-use schemes are few examples of how manufacturing companies are shifting their focus from selling products to offering “solutions”, combining products and services to maximise customer value. The idea of optimising a system towards the best ‘value’ is both “intuitive and sensible”, and processes such as Value Driven Design (VDD), have been proposed to supplement traditional engineering design methodologies. Yet, value-driven initiatives struggle to communicate their benefits and to demonstrate how value models can solve actual problems. The aim of this paper is to shed light on the evolution of the VDD toolbox, mapping research clusters, applications and case studies from the perspective of how much (and how well) recent contributions have answered the five top-level questions of the VDD research agenda published in 2012. The results of the systematic literature review reveal the emergence of innovative modelling constructs, methods, and tools that help VDD in taking a leap forward in supporting organizations and teams in achieving the long-sought objective of designing for 'value'.